Barriers to client-contractor communication: implementing process innovation in a building project in Sweden. (2016) - Engström, Susanne; Stehn, Lars
Client-contractor communication is vital for achieving project goals but also for adopting innovations. However, this type of communication does not take place across just one interface but across several. In the present study, barriers to client-contractor communication were addressed with the intention of specifically highlighting the potential impact of the project-based setting. A case study of a building project where process innovation was to be implemented provided the data. The analysis focused on meaning-making by different participants during progression of the project until its completion. Although the project was successfully completed, some of the aims of the process innovation were not realised as planned due to emerging meaning-making problems. A main suggestion from the reported findings was that the predominant project logic in construction may be a key barrier to client-contractor communication in implementing innovations presented by actors on the supply-side.